Nihilism After Nietzsche - Gillespie, Michael A. (Bollettino Filosofico, 2015)
This essay provides an account of nihilism after Nietzsche, beginning with pre-WW I nihilism, which was associated with decadence and gave rise to an investigation of the primitive, the mythical, and the unconscious. Then I turn to an examination of the nihilistic despair and apocalypticism of the period from the beginning of WW I to the end of WW II. This leads to an examination of nihilism and absurdity in the 1950s and 1960s, before concluding with an examination of nihilism and irony in critical theory and postmodernism. I argue throughout that Nietzsche remains decisive for the later understanding of nihilism and conclude that all attempts to come to terms with nihilism are necessarily inadequate but bring us closer to understanding the uncanny question at its heart.